Intermittency without chaotic shases - Slipushenko, S.V.; Tur, A.V.; Yanovsky, V.V. (Functional Materials, 2006)
A simple map is proposed where the intermitting regime without chaotic phases is appeared. The main characteristics of that intermittent regime have been studied. The distribution function of laminar phase length, Lyapunov exponent and topologic entropy have been derived analytically. The main characteristics have been compared with the computer simulation results.